Development of E-Modules Based on Problem-Based Learning to Improve Students' Problem-Solving Skills in Static Fluid Material - Ardian Ardian; Erniwati Erniwati; Hunaidah M (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aimed to develop an E-module based on problem-based learning on static fluid material to improve the problem-solving abilities of grade XI students. The study used a research and development (R&D) approach with the 4D model consisting of define, design, develop, and disseminate stages. The participants were 40 grade XI students from a public senior high school in Indonesia and two physics teachers involved in assessing the practicality of the E-module. The instruments included validation sheets, practicality questionnaires, and pretest-posttest tests to measure the improvement of students’ problem-solving abilities. Validation by three experts showed a validity score of 92.64% (very valid). Student practicality responses reached 91.76% and 92.41%, while teacher responses reached 94.86%, all categorized as very practical. The effectiveness test showed N-gain scores of 0.76 in class XI.B, 0.77 in class XI.C, and 0.77 overall, which were categorized as high based on Hake’s classification, indicating that the E-module effectively improved students’ problem-solving abilities. The novelty of this study lies in integrating structured problem-based learning activities into a digital E-module for static fluid learning. Overall, the developed E-module is feasible and effective as a digital teaching material to support active, guided, and meaningful physics learning.